Effectiveness of the Crackdown on Illegal Structures Based on Padang Mayor’s Regulation No. 17 of 2015 on the Crackdown on Structures in the Padang Utara Subdistrict - Wahyuni; Afriva Khaidir (Darul Yasin Al Sys, 2026)
Illegal-building control remains a critical issue in public-space governance because urban-order objectives frequently intersect with residents’ livelihood needs. Nevertheless, district-level evidence regarding the effectiveness of local regulations governing illegal structures remains limited. This study analyzed the effectiveness of illegal-building control under Padang Mayor Regulation No. 17 of 2015 in Padang Utara District and identified the factors influencing its implementation. A qualitative descriptive design was employed, involving 12 informants selected through purposive sampling. Data were collected through interviews, observations, and document analysis and analyzed through data reduction, data display, and conclusion drawing, with source triangulation used to strengthen the credibility of the findings. The findings indicate that enforcement was relatively effective across five dimensions of appropriateness: policy, implementation, target, environment, and process. This effectiveness was supported by regulatory clarity, enforcement capacity, institutional coordination, and community participation. However, residents’ economic interests and the recurrence of violations continued to constrain sustained compliance. The study concludes that the effectiveness of illegal-building control depends not only on regulatory and institutional capacity but also on the socioeconomic circumstances of affected residents. These findings provide district-level evidence that durable enforcement requires consistent monitoring, stronger interagency coordination, meaningful community engagement, and livelihood-sensitive implementation strategies.